Reading traces of the past - the Burghöhle Wolfsegg as meeting place for humans, cave lions and co. Spurenlesen in der Vergangenheit - die Burghohle Wolfsegg als Treffpunkt fur Mensch, Hohlenlowe und Co. - Hilpert, Brigitte (Mitteilungen - Verbandes der Deutschen Hohlen- und Karstforscher, 2023)
On the occasion of a tour into the "Burghohle Wolfsegg" in the Franconian Alb (Bavaria), the castle complex was also visited. The faunal remains found there originate from various sites in the cave and are described for the first time. A faunal complex was excavated from the Barenkeller in 1985. The fauna determined here with brown bear (Ursus arctos), cave bear (Ursus spelaeus), cave lion (Panthera leo spelaea) as well as some herbivores can be placed in a rather cool to cold climatic phase of the late Pleistocene around 60,000 - 20,000 years BP. Of particular note is an upper arm bone of a cave lion on which cut marks were found. This is the first such evidence for a cave in the Franconian Alb. Some cut and impact marks on other bones also prove the presence of humans and their impact on animal carcasses or hunted prey. All the material shows traces of various transport phases that led via a former cave room and a shaft step to its current site. At the Rittersaal site, finds were recovered in the 1980s and 1990s. The fauna consists of various domestic animals such as cattle, pigs, sheep/goats, horses and dogs. Wild animals such as red deer (Cervus elaphus) and some predators also occur. Accompanying finds such as pottery shards, a barrel stopper and other human remains prove that the finds can be considered as kitchen waste of the Middle Ages and more recent periods. In 2018, further finds were recovered during the removal of a pile of earth on the wall of the castle building, which are likely to date from the 15th - 17th centuries. In addition to pottery sherds, the find complex consists of fragmented bones of cattle, pig, sheep/goat and horse, with evidence of red deer alongside. Traces of the cutting of the carcasses suggest an interpretation as kitchen waste.
CRIS-Team Scopus Importer:2023-09-22